2021
DOI: 10.1186/s13023-021-01791-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden in the management of transfusion-dependent thalassaemia patients in Malaysia from a societal perspective

Abstract: Background Transfusion-dependent thalassaemia (TDT) is a hereditary blood disorder in which blood transfusion is the mainstay treatment to prolong survival and improve quality of life. Patients with this disease require blood transfusion at more than 100 ml/kg annually and iron-chelating therapy (ICT) to prevent iron overload (IOL) complications. There are substantial numbers of TDT patients in Malaysia, but limited data are available regarding the economic burden associated with this disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The unit costs for out-patient visits and hospitalisation costs were calculated by applying current charges for full fee-paying patients to MOH hospitals (Hospital Putrajaya, 2022;Hospital Selayang, 2022). Transfusion costs were estimated for packed cells, platelet, cross matching and transfusion equipment (Shafie et al, 2021). All HRU unit costs were standardised to index year of 2021.…”
Section: Unit Costmentioning
confidence: 99%
“…The unit costs for out-patient visits and hospitalisation costs were calculated by applying current charges for full fee-paying patients to MOH hospitals (Hospital Putrajaya, 2022;Hospital Selayang, 2022). Transfusion costs were estimated for packed cells, platelet, cross matching and transfusion equipment (Shafie et al, 2021). All HRU unit costs were standardised to index year of 2021.…”
Section: Unit Costmentioning
confidence: 99%
“…Transfusion‐dependent patients are at risk for secondary iron overload, which can accumulate in target organs like the heart, liver, and endocrine glands, leading to high rates of morbidity, mortality, and healthcare resource utilization 2,3,5 . Despite the availability of effective iron chelation therapy, the psychosocial and economic burden of chronic treatment can lead to poor treatment adherence and diminished quality of life 6–11 . Thus, the search for novel therapeutic approaches that can ameliorate the need for transfusion therapy continues 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cost-of-illness studies on TDT have revealed that the costs of lifelong conventional therapy for thalassemia are high and place an enormous economic burden on the healthcare system as well as the patients [16][17][18]. This massive economic burden is majorly attributed to blood transfusions and iron chelation therapy (ICT) [16,[19][20][21][22][23]. Other studies have also revealed that blood transfusion and nursing services and comprise the lion share of the total medical expenditure [24], and that ICT and in-hospital stay are the most expensive components of direct medical cost [12].…”
Section: Introductionmentioning
confidence: 99%